Program, Planning, Budgeting Systems for Educators. Volume I An Instructional Outline. Leadership Series No. 18. - Ohio State Univ., Columbus. Center for Vocational and Technical Education; Ohio State Univ., Columbus. Center for Vocational and Technical Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
Planning, Programming, Budgeting System (PPBS) includes concepts and techniques for resource allocation decision making for rational and effective programming. Most federal agencies use PPBS for the development, analysis and presentation of resource needs. Traditional methods of budgeting focus primarily on resource inputs; PPBS focuses on both inputs (cost) and outputs (benefits). The guidelines in this volume suggest initial training in a sequential pattern for a course in PPBS. Examples used are drawn from the field of vocational education. Included in the instructional outline are sections relating to: (1) Overview, (2) Systems Theory, (3) The Planning Process, (4) Investment Alternatives, (5) Program Budgeting, (6) Analysis of Alternatives, (7) Programming and Management Control, (8) Basic Data for PPBS, and (9) Limitations of PPBS. The document contains three parts: The What-When-Where-Who-Why of This Educational Program, An Educational Training Program in PPBS, and Supplement to the Basic Educational Program. The supplements include pre- and post-tests, a conceptual framework, the relationship of education and economics, and methods of statistical analysis in PPBS. A case problem is announced as VT 009 089. (DM)
Availability: The Center for Vocational and Technical Education, The Ohio State University, 1900 Kenny Road, Columbus, Ohio 43210 ($4.00).
Contract Number: OEG-3-7-000158-2037.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Economics; Illustrations; Models; Program Budgeting; Program Costs; Resource Allocation; Statistical Analysis; Supplementary Reading Materials; Teaching Guides; Textbooks; Transparencies; Cost Effectiveness; Curriculum Guides; Program Development; Systems Approach; Vocational Education; Planning Programming Budgeting System